ENHANCEMENT OF GLIQUIDONE DISSOLUTION THROUGH COMPLEX FORMATION WITH BETA-CYCLODEXTRIN - Prajnadi Liawan, Jeffri
In 2017, as much as 6% of the world's population was diagnosed with type 2 diabetes mellitus, which is expected to increase to 7% in 2030. Gliquidone is an anti-diabetic drug in the sulfonylurea class with a low solubility in water and therefore considered as BCS class 2. This study aimed to investigate the increase in gliquidone dissolution through formation of inclusion complexes with ?cyclodextrin by grinding method. Dissolution test was carried out in phosphate buffer medium at pH 7.4 and measured with UV-Vis spectrophotometer. Dissolution were first tested for powder samples and followed by tablets which were compared with the innovator's product. Complexation methods used are physical mixing and grinding with ball mill. Ball mill method of all duration provided greater dissolution efficiency than physical mixing. Grinding duration used are 30, 60, and 90 minutes. It was found that 60 minutes was the most efficient. Molar ratios of gliquidone:?cyclodextrin of 1:1 and 1:2 did not give a significant difference in dissolution efficiency. Tablets containing inclusion complex from ball milling for 60 minutes experienced an increase in dissolution efficiency of 253% at 1:1 molar ratio compared to pure gliquidone ground at the same duration. Formation of inclusion complex with ?-cyclodextrin was able to increase the dissolution of gliquidone in phosphate buffer at pH 7.4, but it was not equivalent to the dissolution of innovator tablets.